Combining contexts and ontologies: a case study - Rico, Mariela (2006)
In the last years different proposals that integrate ontologies and contexts, taking advantages from their abilities for achieving information semantic interoperability, have arisen. Each of them has considered the problematic from different perspectives. Particularly, through an actual case study this paper shows which are the problems related to support information semantic interoperability between different parties involved in a collaborative business relation over the Internet. Furthermore, this paper analyzes those problems from previous proposals perspective and highlights the weaknesses and strengths of them.